Rothe's method to semilinear hyperbolic integrodifferential equations. (1990) - Bahaguna, D.; Pani, A. K.; Raghavendra, V.
Abstract : In this paper we consider an application of Rothe's method to abstract semi-linear hyperbolic integrodifferential equations in Hilbert spaces. With the aid of Rothe's method we establish the existence of a unique strong solution.